Analysis of the Influence of Knowledge, Technological Progress, Motivation, and Minimum Capital on Generation Z's Investment Interest in the Capital Market - Tia Nur Pangesti; Zulfikar Zulfikar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Investment is an investment activity that is increasingly in demand by the public, especially generation Z. The number of investors in the Indonesian capital market continues to increase, reaching 13 million based on SID at KSEI, with the addition of more than 863 thousand new investors by 2024. The Financial Services Authority and the Indonesia Stock Exchange are working to increase the number of Investment Galleries to support public interest, especially students. Generation Z dominates the capital market, with 57.04% of individual investors under the age of 30. Generation Z's investment interest is influenced by financial literacy and technological advances that facilitate access to information and investment transactions. Digital technology allows investments to be made efficiently without disrupting main activities. Despite the ease of investing, many investors still fail due to a lack of understanding and clear financial goals. Investment motivation in Indonesia is still low due to the lack of financial literacy. In addition, low minimum capital is a motivating factor for students to start investing, especially in stocks at affordable prices. With the characteristics of generation Z who are tech-savvy and like to try new things, investing in the capital market is a great opportunity for them to get long-term benefits. This study aims to determine and analyze knowledge, technological progress, motivation and minimum capital on generation Z's investment interest in the capital market. This research uses quantitative research methods. The results of this study are knowledge, motivation, minimum capital affect investment interest while technological progress has no effect on investment interest.